Marketing Strategy for Football Schools in the City of Cirebon (Case Study of Cirebon United Football School) - Cahyadinata, Joseph Ferdinand; Antomi, Agus; Curatman, Aang (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Football is one of the most popular sports in the world, including in Indonesia. The purpose of this study is to explore and analyze the marketing strategies implemented by the Cirebon United Football School. This research uses a qualitative approach with a case study method. Data collection techniques in this study are literature studies and interviews. The data that has been collected is then analyzed through three stages starting from data reduction, data presentation and conclusions. The results showed that football schools in Cirebon City have implemented various marketing strategies including promotional strategies, pricing strategies, product strategies, and distribution strategies. However, the effectiveness of the marketing strategy still needs to be improved. Football schools need to improve the quality of products and services, the quality of human resources, and the quality of management to improve the effectiveness of marketing strategies.